THE EFFECT OF GADGET AND PARENTING PATTERN ON STUDENTS’ SOCIAL BEHAVIOR AT GRADE V AND VI OF SD PREMBULAN PANDOWAN YOGYAKARTA - Kartiwin; Azam Syukur Rahmatullah; Aris Fauzan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to identify the influence of gadget and parenting pattern on the students’ social behavior at grade V and VI of SD Prembanan Prembulan Pandowan Galur Kulon Progo Yogyakarta, as well as to identify which variable was more influential on students’ social behavior. This research was quantitative research with a total of 55 students of classes V and VI. The data were collected through interviews and questionnaires. The linear regression test resulted in the value of Sig 0.000 which indicated that gadget and parenting pattern were simultaneously influential on students’ social behavior; as seen from the percentage of 94.5%. The t-test of the regression analysis resulted in 8.894 which indicated that the variable of gadget gave an influence on the students’ social behavior. Whilst its significance amounted at 0.000 which indicated that gadget usage gave influence to students’ social behavior to the extent of 69.6%. Furthermore, the t-test on the variable of parenting pattern resulted in 3.323 and the significance value of 0.002. The results indicated that parenting pattern gave an influence on students’ social behavior to the extent of 24.9%